The Ribonuclease P database. - Brown, J W (1994)
The Ribonuclease P Sequence database is a compilation of RNase P sequences, sequence alignments, secondary structures, three-dimensional models, and accessory information. In its initial form, the database contains information on RNase P RNA in bacteria and archaea, and RNase P protein in bacteria. The sequences themselves are presented phylogenetically ordered and aligned. The database also contains secondary structures of bacterial and archaeal RNAs, including specially annotated 'reference' secondary structures of Escherichia coli and Bacillus subtilis RNase P RNAs, a minimum phylogenetic consensus structure, and coordinates for models of three-dimensional structure.